2001
DOI: 10.1128/jb.183.24.7058-7066.2001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Transposon Tn 5367 Mutagenesis and a Nitroimidazopyran-Based Selection System To Demonstrate a Requirement for fbiA and fbiB in Coenzyme F 420 Biosynthesis by Mycobacterium bovis BCG

Abstract: Three transposon Tn5367 mutagenesis vectors (phAE94, pPR28, and pPR29) were used to create a collection of insertion mutants of Mycobacterium bovis strain BCG. A strategy to select for transposon-generated mutants that cannot make coenzyme F 420 was developed using the nitroimidazopyran-based antituberculosis drug PA-824. One-third of 134 PA-824-resistant mutants were defective in F 420 accumulation. Two mutants that could not make F 420 -5,6 but which made the biosynthesis intermediate FO were examined more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 46 publications
(47 reference statements)
2
101
0
Order By: Relevance
“…2B, lanes 4 and 5) and PA-824 sensitivity (Table 1). It has also been reported that inactivation of the fbiA (Rv3261) or fbiB (Rv3262) genes in M. bovis lead to an accumulation of FO with concomitant loss of F 420 (11). Therefore, mutant 7A2 was complemented with the fbiAB operon, restoring normal levels of F 420 biosynthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B, lanes 4 and 5) and PA-824 sensitivity (Table 1). It has also been reported that inactivation of the fbiA (Rv3261) or fbiB (Rv3262) genes in M. bovis lead to an accumulation of FO with concomitant loss of F 420 (11). Therefore, mutant 7A2 was complemented with the fbiAB operon, restoring normal levels of F 420 biosynthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies had established that loss of FGD1 or the loss of biosynthetic potential for F 420 individually resulted in resistance to PA-824 (6,10,11). To establish whether FGD1 or reduced F 420 interacted with PA-824 directly, we partially purified recombinant Mtb-FGD1 from Escherichia coli and incubated this with oxidized F 420 purified from Mycobacterium smegmatis (see Supporting Text, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…In the first, a riboflavin precursor (5-amino-6-(D-ribitylamino)uracil) is condensed with tyrosine to form 8-hydroxy-5-deazaflavin, also known as F o ; this step is catalyzed by the radical S-adenosylmethionine enzymes CofG and CofH that are fused into a single protein in some bacteria (known as CofGH or FbiC) (Choi et al, 2002;Philmus et al, 2015). Subsequently, LPPG (L-lactyl-2-diphospho-5 0 -guanosine) is proposed to be synthesized from 2-phospho-L-lactate by CofC (Grochowski et al, 2008) and transferred to F o by CofD (also known as FbiA) (Choi et al, 2001;Graupner and White, 2001;Graupner et al, 2002). The resulting LPPG sidechain is finally elongated with glutamate residues by the F 420 :γ-L-glutamyl ligase CofE (also known as FbiB) (Choi et al, 2001;Li et al, 2003;Nocek et al, 2007) that is fused with an FMNdependent oxidoreductase in Actinobacteria (Bashiri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, LPPG (L-lactyl-2-diphospho-5 0 -guanosine) is proposed to be synthesized from 2-phospho-L-lactate by CofC (Grochowski et al, 2008) and transferred to F o by CofD (also known as FbiA) (Choi et al, 2001;Graupner and White, 2001;Graupner et al, 2002). The resulting LPPG sidechain is finally elongated with glutamate residues by the F 420 :γ-L-glutamyl ligase CofE (also known as FbiB) (Choi et al, 2001;Li et al, 2003;Nocek et al, 2007) that is fused with an FMNdependent oxidoreductase in Actinobacteria (Bashiri et al, 2016). For reasons still not understood, the number of glutamate residues added varies between organisms, ranging from two to three in most methanogens (Gorris and van der Drift, 1994), four to five in Methanosarcina (Gorris and van der Drift, 1994) and five to seven in Mycobacterium .…”
Section: Introductionmentioning
confidence: 99%
“…FbiA and FbiB are enzymes that catalyze steps in the biosynthesis of F 420 downstream of FO synthase (48). Searches of the Chlamydomonas genome revealed no genes encoding putative homologs of FbiA and FbiB.…”
Section: Discussionmentioning
confidence: 99%